Mummification Of The Human Body For Medical Education: A Comparative Analysis Of The Methods - Meena, Rajesh Kumar; Mohan, Mukta Mala; Nama, Devendra Kumar; Mathur, Astha; Choudhary, Himani; Modiyani, Neha; Alawa, Viraj; Gupta, Soni (Journal of Neonatal Surgery, 2025)
Mummification is the method of embalming the dead body during the period of ancient Egyptians era. Different methods for mummification are ancient method, chinchoro method (The Black Mummy Technique, The Red Mummy Technique, The bandaged mummies), sokushinbutsu method, modern Method (Arterial embalming, Cavity embalming, Hypodermic embalming Hypodermic embalming, Surface embalming). Plastination is a scientific method or process used in anatomy and forensic medicine departments for medical teaching that preserves the body or body parts